Ways to Prepare for the Profession by Inculcating a Healthy Lifestyle in the Minds of Students : Ways to Prepare for the Profession by Inculcating a Healthy Lifestyle in the Minds of Students - Xaydarov, Ilhom (Физическое воспитание, спорт и здоровье, 2021)
Introducing a healthy lifestyle among students in the article Ways to form a healthy lifestyle in our country in this regard the work being done is therefore to keep students healthy,organize a healthy lifestyle in preparation for a harmonious and professional life factors (material, spiritual, mental, physical, intellectual,values) and their relevance in the content of education a systematic approach should apply the research method and adhere to them